Pemaksimalan Media Pembelajaran Untuk Pembelajaran Daring Pada SDN 9 Dauh Puri Denpasar Bali - Luh Made Yulyantari; Ni Kadek Sumiari; Ni Luh Nyoman Mirah Wedasari (Jurnal Ilmiah Pangabdhi, 2021)
The world of education underwent major changes in 2020 due to the Covid-19 pandemic. The most visible impact of changes in the world of education in the midst of the Covid-19 pandemic is the effectiveness of the teaching and learning process that has turned online. One of the elementary schools that experienced these changes was SD N 9 Dauh Puri, North Denpasar. Online learning is currently being carried out at SD N 9 Dauh puri using WhatsApp and Google classroom media. However, in practice, teachers still use personal accounts in the use of online learning media, so the features of these learning media cannot be utilized optimally. In addition, the teachers also do not understand optimally in the use of these learning media. Based on these problems, through this service activity, assistance is provided in creating an account with a free domain provided by the government (.sch) as well as the school website. Other activities include training on the use of Google Forms as a medium for collecting assignments and evaluating learning. The implementation method of service activities consists of socializing activities, planning, implementing, and evaluating. The outputs of community service activities have met the achievement indicators, namely all teachers (100%) already have an email account with a domain (sch.id) owned by the school and the school already has a website installed on the http://www.sdn9dauhpuri.sch page. id/. The results of the assessment from partners, 74% stated that community service activities were satisfactory.